2020
DOI: 10.1126/sciadv.aba1269
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle of a cyanobacterial carboxysome

Abstract: Carboxysomes, prototypical bacterial microcompartments (BMCs) found in cyanobacteria, are large (~1 GDa) and essential protein complexes that enhance CO2 fixation. While carboxysome biogenesis has been elucidated, the activity dynamics, lifetime, and degradation of these structures have not been investigated, owing to the inability of tracking individual BMCs over time in vivo. We have developed a fluorescence-imaging platform to simultaneously measure carboxysome number, position, and activity over time in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 29 publications
2
56
0
Order By: Relevance
“…While α-and β-carboxysome aggregation does not result in a high CO2-requiring phenotype (MacCready et al, 2018; Desmarais et al, 2019), we recently found that β-carboxysome aggregation in S. elongatus does result in slower cell growth, cell elongation, and asymmetric cell division; presumably due to decreased carbon-fixation by RuBisCO in these aggregates (Rillema et al, 2020). Moreover, it was recently found that degradation of inactive carboxysomes occurs at polar regions of a cyanobacterial cell (Hill et al, 2020). How the polar localization of carboxysome aggregates, from a lack of a McdAB system, influences carboxysome function and turnover remains unclear.…”
Section: Mcda and Mcdb Maintain Carboxysome Distributions In H Neapomentioning
confidence: 99%
“…While α-and β-carboxysome aggregation does not result in a high CO2-requiring phenotype (MacCready et al, 2018; Desmarais et al, 2019), we recently found that β-carboxysome aggregation in S. elongatus does result in slower cell growth, cell elongation, and asymmetric cell division; presumably due to decreased carbon-fixation by RuBisCO in these aggregates (Rillema et al, 2020). Moreover, it was recently found that degradation of inactive carboxysomes occurs at polar regions of a cyanobacterial cell (Hill et al, 2020). How the polar localization of carboxysome aggregates, from a lack of a McdAB system, influences carboxysome function and turnover remains unclear.…”
Section: Mcda and Mcdb Maintain Carboxysome Distributions In H Neapomentioning
confidence: 99%
“…Beyond a potential role in dynamics, increased shell flexibility could allow for packing a greater variety of internal enzymes in non-carboxysomal MCPs, or more variable enzyme stoichiometries. The processes that govern MCP assembly and disassembly remain only partially understood, 15,[54][55][56][57] and flexibility could be important for those processes. The flexibility observed in this protein family invites additional questions about microcompartment structure, evolution, and function.…”
Section: Discussionmentioning
confidence: 99%
“…CA generates a high CO 2 concentration in the carboxysome. Shell breakage may cause carboxysome loss in cyanobacteria [4]. C4 plants like maize employ a CO 2 concentration mechanism where HCO 3 − is fixed by phospho-enol-pyruvate carboxylase (PEPC) in the mesophyll to produce oxaloacetate, which is reduced to malic acid with NADH + H + as an electron donor.…”
Section: Introductionmentioning
confidence: 99%
“…CA generates a high CO 2 concentration in the carboxysome. Shell breakage may cause carboxysome loss in cyanobacteria [ 4 ].…”
Section: Introductionmentioning
confidence: 99%